Probability on algebraic and geometric structures - International Research Conference in Honor of Philip Feinsilver, Salah-Eldin A. Mohammed, and Arunava Mukherjea (Carbondale, Illinois 5-7 June 2014); Budzban, Gregory; Hughes, Harry Randolph; Schurz, Henri (Providence : American Mathematical Society, 2016)
This volume contains the proceedings of the International Research Conference "Probability on Algebraic and Geometric Structures", held from June 5-7, 2014, at Southern Illinois University, Carbondale, IL, celebrating the careers of Philip Feinsilver, Salah-Eldin A. Mohammed, and Arunava Mukherjea. These proceedings include survey papers and new research on a variety of topics such as probability measures and the behavior of stochastic processes on groups, semigroups, and Clifford algebras; algebraic methods for analyzing Markov chains and products of random matrices; stochastic integrals and stochastic ordinary, partial, and functional differential equations.
* A. Anckar and G, Hognas, The fine structure of the stationary distribution for a simple Markov process* D. Bell, Superdegenerate hypoelliptic differential operators* G. Budzban and A. Mukherjea, Some remarks on the convolution equation $\mu*\beta=\mu$ and product semigroups* S. Chakraborty, Limit distributions of products of i.i.d. random $2x2$ stochastic matrices: An open problem* A. Cosso, C. Di Girolami, and F. Russo, Calculus via regularizations in Banach spaces and Kolmogorov-type path-dependent equations* P. Feinsilver, Matrices with zero row sums, tree theorems and Markov chain on trees* P. Graczyk and P. Sawyer, Convolution of orbital measures on symmetric spaces: A survey* G. Hognas and B. Jung, Exit times for some autoregressive processes with non-Gaussian noise distributions* I. Kemajou-Brown, Brief history of optimal control theory and some recent developments* J. Kocik, Krawtchouk matrices, Feynman path integral and the split quaternions* R. Leandre, The Ito-Stratonovich formula for an operator of order four* C. R. E. Raja and R. Schott, Random walks on motion groups* H. Schurz and A. Talafha, Existence, uniqueness, and energy of modified stochastic sine-Gordon equation with multiplicative noise on one-dimensional domain* L. Siriwardena and H. R. Hughes, Squared Bessel process with delay* G. S. Staples, Kravchuk matrices and induced operators on Clifford algebras.
Includes bibliographical references.
Keywords: Probability measures -- Congresses; Combinatorial geometry -- Congresses; Differential equations -- Congresses; Markov processes -- Congresses